2006
DOI: 10.1002/hbm.20234
|View full text |Cite
|
Sign up to set email alerts
|

Toward brain correlates of natural behavior: fMRI during violent video games

Abstract: Modern video games represent highly advanced virtual reality simulations and often contain virtual violence. In a significant amount of young males, playing video games is a quotidian activity, making it an almost natural behavior. Recordings of brain activation with functional magnetic resonance imaging (fMRI) during gameplay may reflect neuronal correlates of real-life behavior. We recorded 13 experienced gamers (18-26 years; average 14 hrs/week playing) while playing a violent first-person shooter game (a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
122
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(136 citation statements)
references
References 50 publications
10
122
1
3
Order By: Relevance
“…A meta-analytic review seems to support this opinion (28). Moreover, several current studies revealed that virtual violence may lead to desensitization in real life, partly confirming these assumptions using fMRI (29). These studies show that the act of killing virtually is connected with a decreasing potential in regions of the brain which are associated with empathy.…”
Section: Violence In Computer Gamessupporting
confidence: 67%
“…A meta-analytic review seems to support this opinion (28). Moreover, several current studies revealed that virtual violence may lead to desensitization in real life, partly confirming these assumptions using fMRI (29). These studies show that the act of killing virtually is connected with a decreasing potential in regions of the brain which are associated with empathy.…”
Section: Violence In Computer Gamessupporting
confidence: 67%
“…Activity in the medial prefrontal cortex has been widely reported in studies using emotional tasks or stimuli, whereas activity in the adjacent ACC was more specifically related to emotional tasks with a cognitively demanding component (Phan et al, 2002;Mathiak and Weber, 2006). In addition, the well documented role of the ACC in cognitive conflict resolution (Kerns et al, 2004), which has also recently been demonstrated in the context of conflicting emotional stimuli (Müller et al, 2011), is likely to contribute to this part of the network.…”
Section: Discussionmentioning
confidence: 94%
“…The concern is that if we have begun to figure out how a video game or digital game improves cognition in players or naive people by bettering attention, and how are reaction times on "making a decision" and memory without using the conventional or violent video games [46]. [47].…”
Section: Discussionmentioning
confidence: 99%